Increase in prevalence of current mental disorders in the context of COVID-19: analysis of repeated nationwide cross-sectional surveys - Winkler, P; Formanek, T; Mlada, K; Kagstrom, A; Mohrova, Z; Mohr, P; Csemy, L (Epidemiology and psychiatric sciences, 2020)
AIMS: The United Nations warned of COVID-19-related mental health crisis; however, it is unknown whether there is an increase in the prevalence of mental disorders as existing studies lack a reliable baseline analysis or they did not use a diagnostic measure. We aimed to analyse trends in the prevalence of mental disorders prior to and during the COVID-19 pandemic. METHODS: We analysed data from repeated cross-sectional surveys on a representative sample of non-institutionalised Czech adults (18+ years) from both November 2017 (n = 3306; 54% females) and May 2020 (n = 3021; 52% females). We used Mini International Neuropsychiatric Interview (MINI) as the main screening instrument. We calculated descriptive statistics and compared the prevalence of current mood and anxiety disorders, suicide risk and alcohol-related disorders at baseline and right after the first peak of COVID-19 when related lockdown was still in place in CZ. In addition, using logistic regression, we assessed the association between COVID-19-related worries and the presence of mental disorders. RESULTS: The prevalence of those experiencing symptoms of at least one current mental disorder rose from a baseline of 20.02 (95% CI = 18.64; 21.39) in 2017 to 29.63 (95% CI = 27.9; 31.37) in 2020 during the COVID-19 pandemic. The prevalence of both major depressive disorder (3.96, 95% CI = 3.28; 4.62 v. 11.77, 95% CI = 10.56; 12.99); and suicide risk (3.88, 95% CI = 3.21; 4.52 v. 11.88, 95% CI = 10.64; 13.07) tripled and current anxiety disorders almost doubled (7.79, 95% CI = 6.87; 8.7 v. 12.84, 95% CI = 11.6; 14.05). The prevalence of alcohol use disorders in 2020 was approximately the same as in 2017 (10.84, 95% CI = 9.78; 11.89 v. 9.88, 95% CI = 8.74; 10.98); however, there was a significant increase in weekly binge drinking behaviours (4.07% v. 6.39%). Strong worries about both, health or economic consequences of COVID-19, were associated with an increased odds of having a mental disorder (1.63, 95% CI = 1.4; 1.89 and 1.42, 95% CI = 1.23; 1.63 respectively). CONCLUSIONS: This study provides evidence matching concerns that COVID-19-related mental health problems pose a major threat to populations, particularly considering the barriers in service provision posed during lockdown. This finding emphasises an urgent need to scale up mental health promotion and prevention globally.
Keywords: Cross-Sectional Studies; Male; poruchy způsobené alkoholem; Middle Aged; Alcohol-Related Disorders; úzkostné poruchy; Mental Disorders; Česká republika; Mental Health; Depressive Disorder, Major; Adult; koronavirové infekce; prevalence; dospělí; duševní zdraví; mužské pohlaví; sebevražda; Betacoronavirus; pandemie; duševní poruchy; průzkumy a dotazníky; SARS-CoV-2; Mood Disorders; Czech Republic; poruchy nálady; virová pneumonie; lidé; Suicide; ženské pohlaví; Anxiety Disorders; Humans; depresivní porucha unipolární; průřezové studie; Prevalence; mental disorders; Pneumonia, Viral; Pandemics; suicide risk; psychiatrické posuzovací škály; Coronavirus Infections; Female; Psychiatric Status Rating Scales; lidé středního věku; Surveys and Questionnaires; Anxiety; depression; COVID-19